China’s Public Diplomacy Through the Utilization of Investment and Censorship in Hollywood (2012 – 2016) - Baskoro, Riski M; Theresia, Amalia Agustina; Raharyo, Anggara (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
The conduct of traditional public diplomacy was merely concerned on the engagement of state actors. Not to mention, diplomatic communication is only occurred between the government officials by intention to earned political changes in targeted countries. Recently, public diplomacy is mainly focused on the positive reputation building in the other country and is conducted through political and economic cooperation among two countries or more, by involving the non-state actors also. Starting from its economic reforms initiative, China is engaged in international trade and successfully became one of global economic powers. By its rapid raise, China is feared to be a national threat to other countries, be it politically, economically, or even for the national security. Even more, the Western media often portrays China?s image in a negative light. Hence, in improving its global image, China expands its global outreach by establishing cooperation with the United States film industry, Hollywood, that strengthen by the 2012?s Memorandum of Understanding upon film industry, also by implementing Chinese censorship policy, where negative portrayals of China is prohibited. The conduct of censorship itself would be supervised under state-ruled agency, the SAPPRFT, and is supported by the involvement of Chinese multinational companies investors. Through this research study, the effort of China?s public diplomacy on the utilization of Hollywood as the United States film industry would be proven through new public diplomacy theory. Further, the role of multinational corporations will be assessed due to its essential contribution in enhancing Chinese censorship in Hollywood films for its global release.